2004
DOI: 10.1136/gut.2003.021105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peroxisome proliferator activated receptor   ligands on growth and gene expression profiles of gastric cancer cells

Abstract: Background and aims: Although peroxisome proliferator activated receptor c (PPARc) agonists have been implicated in differentiation and growth inhibition of cancer cells, the potential therapeutic and chemopreventive effects on gastric cancer are poorly defined. We examined the in vitro and in vivo effects of PPARc ligands on growth of gastric cancer, and the effect of PPARc activation on expression of cyclooxygenase 2 (COX-2) and cancer related genes. Methods: Gastric cell lines (MKN28 and MKN45) were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 35 publications
3
42
1
Order By: Relevance
“…PPARg, activated by statins (32), suppresses proinflammation gene expression (42). This study showed that pitavastatin treatment decreased serum leptin levels and increased PPARg activity in the intestinal mucosa and the liver.…”
Section: Discussionmentioning
confidence: 79%
“…PPARg, activated by statins (32), suppresses proinflammation gene expression (42). This study showed that pitavastatin treatment decreased serum leptin levels and increased PPARg activity in the intestinal mucosa and the liver.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, PPARg ligands have been shown to inhibit transcriptional activation of COX-2 in human epithelial cells (Badawi et al, 2004). In certain cancer cells, ligand activation of PPARg results in the inhibition of the release of inflammatory cytokines by cancer cells (Leung et al, 2004). These results may help to explain the shuttling of PPARg expression from the cytoplasm to nucleus with the progression of ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 83%
“…In another study, loss of PPARg was shown not to affect mammary development and propensity for tumour formation but resulted in reduced fertility (Cui et al, 2002). Overall, ligand activation of PPARg in tumour models can result in diversified functional outcome (Leung et al, 2004) and a better understanding of the exact role of PPARg in cancer needs to be determined. In particular, the mechanism of differentiation of cancers is incompletely understood and an insight into this process would undoubtedly lead to new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding to PPAR activates the transcription of PPAR responsive genes including cellular development, differentiation and carcinogenesis. PPARγ gene expression was identified in both gastric cancerous and normal gastric epithelium (Leung et al, 2004). It has also been shown activation of PPARγ inhibits the growth and induces apoptosis of gastric cancer cells (Leung et al, 2004).…”
Section: Discussionmentioning
confidence: 99%